Supervision of Standard Operating Procedures (SOP) in Early Childhood Education Learning (Journal of Primary Education, 2019)
This study aims to determine effort in improving the quality of teacher competenes in Pre-School institutions; to describe the use of learning management Standard Operating Procedures (SOP); as well as to describe the quality of learning management. Data in the form of suggestions and reasons were analyzed using qualitative analysis. The results of the study are teacher performance in Pre-School institutions can be improved by implementing SOP on learning management, the use of SOP affects the quality of learning in Pre-School, measurement of teacher performance in a Pre-School institution after applying SOP on learning management with 80% results in good category, teacher responses to the developed learning management SOP show good responses, provide convenience. The study concludes that the importance of SOP on learning management for quality of early childhood services, the program process is still lacking because in the aspect of SOP implementation there is still a lack of smoothness and awareness of the program teacher is still minimal, the product program is quite good, because it provides convenience in working, program evaluation is carried out with supervision activities and filling out an assessment form from the school principal. Assessment tools as supervision sheets must be available to assess teacher performance. The principal as a supervisor, carries out classroom supervision activities by observing and monitoring teaching and learning activities in schools. Some important things in supervision by school principals are related to discipline, creativity, innovation, effective ways of communication, responsibility and accuracy of teachers in using learning media.